Uso de metodologias ativas no ensino de entomologia no ensino médio - Leal, Silvia Cavalcanti (2020)
The current Biology Teaching demands teachers innovating in their pedagogical practice using active methodologies that contribute effectively to the teaching-learning process. In this context, there was the planning of a didactic sequence that sought to promote Scientific Literacy through teaching by investigation and that contributed to the construction and dissemination of scientific knowledge about insects. Thus, with this research, it was intended to improve the teaching on Entomology in High School from the use of active methodologies. Thus, a didactic sequence was planned and applied with a class from the 2nd year of regular high school at the Francisco Apolinário da Silva State Elementary and High School, located in the municipality of Areial, state of Paraíba, targeting 31 students. The work is an action research of an applied nature with a qualitative and quantitative approach. As a tool for obtaining data, a pre-test questionnaire was applied that analyzed the students' prior knowledge, as well as a post-test questionnaire that was applied after the strategies and methodological approaches used and, thus, it was possible to evaluate the effectiveness activities produced and applied with students in the teaching-learning process. Activity planning included: (1) practical activities, (2) field activity, (3) laboratory activity with an investigative approach and (4) poster making to compose a mural about insects and socializing the theme. As a result, most of the responses obtained through the questionnaires were categorized by content analysis. It was evident that students developed skills to manipulate, question, investigate, organize and communicate and that there was a greater learning about the morphological characteristics of insects relating them to their eating and living habits, as well as the ecological, economic and medical importance of insects. Thus, it was found that when studying insects within a context that involves their ecological relationships, using active methodologies, opinions of a predominantly negative character as those evidenced in some pre-test responses are diluted, yielding space for opinions that incorporate the ecological aspects of insects. Therefore, after the active methodologies used in classes, greater learning took place, since the post-test responses showed an evolution in the levels of Scientific Literacy. The students provided more complex answers, as well as, adequate explanations of the scientific concepts, demonstrating a comprehensive understanding of insects, thus reinforcing the importance of using active methodologies in Biology classes as a way to improve the teaching of Entomology in High School. The planning and application of the didactic sequence resulted in a final product that accompanies this research. Thus, the product that consists of a didactic sequence, will serve as a didactic resource that will assist teaching practice, through the suggestion of activities to develop the content of Entomology in High School through active methodologies. Thus, the didactic sequence will facilitate the teaching-learning process of the theme through an investigative and contextualized teaching.